2020
DOI: 10.1101/2020.07.23.217893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retinal optic flow during natural locomotion

Abstract: Here we examine the ways that the optic flow patterns experienced during natural locomotion are shaped by the movement of the observer through their environments. By recording body motion during locomotion in natural terrain, we demonstrate that head-centered optic flow is highly unstable regardless of whether the walker’s head (and eye) is directed towards a distant target or at the ground nearby to monitor foothold selection. In contrast, VOR-mediated retinal optic flow has stable, reliable features that may… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 101 publications
0
43
0
Order By: Relevance
“…The same areas are also involved in the control of smooth pursuit eye movements (Lisberger, 2015) and saccades to moving targets (Newsome, Wurtz, Dusteler, & Mikami, 1985). In the absence of explicit instruction or other tasks, looking at the FOE might generate a radial flow of visual information that is in line with what we experience in everyday life (where the retinal FOE is centered to straight ahead, Matthis, Muller, Bonnen, & Hayhoe, 2020).…”
Section: Intuitive Tracking Is Sensitive To Stimulus Featuresmentioning
confidence: 81%
See 1 more Smart Citation
“…The same areas are also involved in the control of smooth pursuit eye movements (Lisberger, 2015) and saccades to moving targets (Newsome, Wurtz, Dusteler, & Mikami, 1985). In the absence of explicit instruction or other tasks, looking at the FOE might generate a radial flow of visual information that is in line with what we experience in everyday life (where the retinal FOE is centered to straight ahead, Matthis, Muller, Bonnen, & Hayhoe, 2020).…”
Section: Intuitive Tracking Is Sensitive To Stimulus Featuresmentioning
confidence: 81%
“…Our work shows that human observers track FOE changes even when they are not explicitly instructed to do so, suggesting that this tracking behavior is intuitive. The ability to keep the eyes aligned with a shifting FOE might serve as an important gaze stabilization strategy during self-motion, facilitating the control of the body during natural locomotion, and compensating for the unstable flow experienced when the head moves rhythmically during a gait cycle (Matthis, Muller, Bonnen, & Hayhoe, 2020). Furthermore, we show that this intuitive tracking behavior shares many characteristics (e.g., overall alignment and sensitivity to motionsignal-strength manipulation) with instructed performance, supporting the use of intuitive eye movements as sensitive indicators of visual motion processing.…”
Section: Resultsmentioning
confidence: 99%
“…Our work shows that human observers track FOE changes even when they are not explicitly instructed to do so, suggesting that this tracking behavior is intuitive. The ability to keep the eyes aligned with a shifting FOE might serve as an important gaze stabilization strategy during self-motion, facilitating control of the body during natural locomotion and compensating for the unstable flow experienced when the head moves rhythmically during a gait cycle ( Matthis et al, 2020 ). Furthermore, we have shown that this intuitive tracking behavior shares many characteristics (e.g., overall alignment and sensitivity to motion-signal-strength manipulation) with instructed performance, supporting the use of intuitive eye movements as sensitive indicators of visual motion processing.…”
Section: Discussionmentioning
confidence: 99%
“…The same areas are also involved in the control of smooth-pursuit eye movements (Lisberger, 2015) and saccades to moving targets (Newsome, Wurtz, Dürsteler, & Mikami, 1985). In the absence of explicit instructions or other tasks, looking at the FOE might generate a radial flow of visual information that is in line with what we experience in everyday life, where the retinal FOE is centered to straight ahead (Matthis, Muller, Bonnen, & Hayhoe, 2020).…”
Section: Intuitive Tracking Was Sensitive To Stimulus Featuresmentioning
confidence: 95%
“…Between optic flow and mechanical layout, standing still relies on synergies spanning the limbs and joints at smaller scales and subtle postural perturbations, triggering reflex arcs and muscle twitches, at yet smaller scales. The task of standing still and visually fixating laces together activities at these multiple scales, entailing a close connection among events of widely varying scales, from whole-body postural fluctuations at large scales, to head sway and eye movements at medium scales, and photoreceptor activity at the finest scales [13]. Consequently, the postural center of pressure (CoP) fluctuations—which directly relate to sway—exhibit similar statistical signatures of cascade dynamics as found in fluid flow [4].…”
Section: Introductionmentioning
confidence: 99%